Migration magnet: The role of work experience in rural-urban wage differentials - Maren Michaelsen; John Haisken-DeNew (IZA Journal of Migration, 2015)
This study uses the nationally representative Mexican Family Life Survey (MxFLS) to identify systematic differences in earnings returns to human capital endowments for formal and informal sector workers in rural and urban Mexico. Returns to experience are critical in explaining the large urban wage gap in a Blinder-Oaxaca decomposition and indeed drive pull migration from the rural informal sector to the urban informal sector, exacerbating urban population congestion in already over-crowded main cities. Targeted rural industrial planning is essential to offset pull migration and ensure a more balanced urban/rural development through incentives.
Keywords: J24; J31; R23; Q15; 330; Returns to experience; Rural-urban wage differentials; Formal/informal sector; Internal migration; Mexico